FORMULATION AND PHYSICO-CHEMICAL CHARACTERISATION OF KSHARAPLOTA DRESSING FOR VRANA CHIKITSA (International Journal of Ayurveda and Pharma Research, 2018)
Good quality of wound healing is a difficult task to the clinicians in ancient time and even in present time though. Wound healing is a defense mechanism of our body to prevent and fight against infection. In Health sciences, wound healing formulations are practiced with their own advantage and disadvantages. Ayurveda is a divine science of medicine where there are so many pieces of diamonds available for management of Vrana without any complication. Our Acharyas broadly described about treatment principles of wound management and classified the drugs related to Vranashodhana and Vranaropana. As per text we are well known about the wider approach of Acharya Sushruta in relation to Vrana and its management. They have mentioned various dressing materials for wound care it comprises Pichu, Plots, Kawalika, etc. Among these Plota is much better because we can use it for both purposes i.e. to clean as well as to cover the wound.Ksharaplota (medicated gauze) is an innovative and newer concept used for management of Infected and chronic Wounds and ulcers. This Ksharaplota is a herbo-chemical compound and prepared with the help of Snuhikshira (milk of Euphorbia neriifolia Linn.), Apamargakshara (ash of Achyranthes aspera L.) and Haridra (Curcuma longa L.). A single coating of the above drugs were given to the Plota (gauze). It can be used in number of open wounds and ulcers. This Ksharaplota was prepared similarly with basic concept of Ksharsutra preparation. The Aim of this study was to formulate Ksharaplota dressing and to do the physico-chemical analysis of the Ksharaplota. The proved that pharmaceutical processing of the raw drugs imparts characteristic property to the formulation were evident by the physicochemical analysis of the Ksharaplota. The method of formulation of Ksharaplota holds good even for today’s era and can be considered as standard protocol for Vrana Shodhana and Ropana in Dushta Vrana Chikitsa.